From patient uncertainty to WHO policy in two years: A GP's experience of preparing and maintaining a Cochrane review*. (March 2014) - Irving, Greg
Abstract: Clinical encounters in daily practice can provide a fertile ground for identifying uncertainties that require further investigation. Addressing such uncertainties by undertaking a Cochrane review can be a rewarding educational process and result in important contributions to health care policy. This paper describes the experiences of a UK GP undertaking a Cochrane review whilst working in clinical practice. It outlines some of the practical issues when starting a review, the importance of effective mentorship and collaboration, the power of the modern medical media (BMJ, Wikipedia) and engaging with policy makers (WHO).